The Economics of Carbon Dioxide Removal: A Governance Perspective - Ottmar Edenhofer; Max Franks; Friedemann Gruner; Matthias Kalkuhl; Kai Lessmann (CESifo GmbH, 2024)
Carbon dioxide removal (CDR) is becoming an emerging topic in climate policy. We review the nascent economic literature on the governance of CDR and discuss policy design and institutions. We first assess the role of CDR in climate policy portfolios that include abatement and adaptation. Cost saving technological progress could make CDR a game changer in climate policy: CDR creates new sectoral, intertemporal and international flexibilities, which reduce overall costs and allow returning to a temperature target after temporary overshooting. Moreover, carbon removal can reduce the problem of international cooperation due to substantially lower supply-side leakage via fossil fuel markets. A key challenge lies in its governance and incentive structure that is complicated by non-permanence of carbon storage and default risks of the firms committed to future CDR. For CDR governance, we survey approaches that incentivize removals by price instruments or include CDR in (modified) emissions trading schemes.
Keywords: H23; Q54; Q58; 330; CO2-Speicherung; Treibhausgas-Emissionen; Luftreinhaltung; Technischer Fortschritt; Mechanismus-Design-Theorie